Temporal-spatial distribution of the hermit crab Loxopagurus loxochelis (Decapoda: Diogenidae) from Ubatuba Bay, São Paulo State, Brazil - Mantelatto, Fernando L.M. (2004)
The present work was conducted to determine the distribution of Loxopagurus loxochelis collected monthly, over a period of one year, in Ubatuba Bay (from September/95 to August/96). A total of 179 specimens were collected (138 males, 30 females and 11 ovigerous females). The greatest depth, predominance of very fine sand and highest mean value of organic matter contents of sediment, in combination with the low temperatures registered in winter (July and August), determined the presence of L. loxochelis in the subarea located at the Ubatuba Bay mouth, exposed to the open sea with high water current energy, important because this position insures that spawned larvae will enter into the oceanic circulation.